PENGGUNAAN TELEHEALTH DALAM PELAYANAN KEPERAWATAN KEPADA ORANG DENGAN HIV- AIDS/ ODHIV: TELAAH JURNAL - Isnaeni Nur Khayati; Tuti Herawati (Bajang Institute, 2022)
Introductions: People living with HIV/AIDS/PLWH is increasing every year. This phenomenon requires good handling so that the number does not increase and get out of control. Telehealth is information technology in health and nursing services for people living with HIV. Objective: This study aims to examine the use o/f telehealth applications in health services to people with HIV/AIDS. Methods: The literature review used in this study utilizes online databases: Scopus, Science Direct, and ProQuest. The keywords used in the search engine are HIVAIDS, telehealth, nursing care. Results: Searching for journals using an online database resulted in several journals, then picking up eight journals to review. The results show that applying telehealth in health services for people with HIV AIDS has been used in all parts of the world. The telehealth technology used includes the use of landlines, cell phones, the internet, and social media. The influence that occurs due to telehealth is quite varied with attitudes and decision maker of people with HIV. Conclusion: Telehealth can be used as a medium to provide health and nursing services to people with HIV AIDS.